Energetic particle induced intra-seasonal variability of ozone inside the Antarctic polar vortex observed in satellite data - Fytterer, Tilo; Mlynczak, Martin G.; Nieder, H.; Perot, Kristell; Sinnhuber, M.; Stiller, G.; Urban, Joachim (Atmospheric Chemistry and Physics, 2015)
Measurements from 2002 to 2011 by three inde-pendent satellite instruments, namely MIPAS, SABER, andSMR on board the ENVISAT, TIMED, and Odin satellitesare used to investigate the intra-seasonal variability of strato-spheric and mesospheric O3 volume mixing ratio (vmr) in-side the Antarctic polar vortex due to solar and geomagneticactivity. In this study, we individually analysed the relativeO3 vmr variations between maximum and minimum condi-tions of a number of solar and geomagnetic indices (F10.7cm solar radio flux, Ap index, ≥2 MeV electron flux). Theindices are 26-day averages centred at 1 April, 1 May, and1 June while O3 is based on 26-day running means from1 April to 1 November at altitudes from 20 to 70 km. Dur-ing solar quiet time from 2005 to 2010, the composite ofall three instruments reveals an apparent negative O3 sig-nal associated to the geomagnetic activity (Ap index) around1 April, on average reaching amplitudes between −5 and−10 % of the respective O3 background. The O3 responseexceeds the significance level of 95 % and propagates down-wards throughout the polar winter from the stratopause downto ∼ 25 km. These observed results are in good qualitativeagreement with the O3 vmr pattern simulated with a three-dimensional chemistry-transport model, which includes par-ticle impact ionisation.